Gestión Administrativa En La Recaudación De Los Tributos Y Su Influencia En El Grado De Cumplimiento De Obras En El Gad Municipal Del Cantón Baba Periodo 2015-2017 - Posligua Aguilar, Tatiana Vanessa (2018)
n the city of Baba, Province of Los Ríos, the research was conducted entitled: "Administrative management in the collection of taxes and their influence on the degree of compliance of works of the Municipal GAD Baba Canton 2015-2017 period", whose objective The main one is to analyze the incidence of administrative management in the fulfillment of the works. The specific objectives were aimed at determining the factors that intervene in the collection of taxes for the degree of compliance with works, establish the administrative management of tax collection and propose administrative management strategies that encourage the collection of taxes for the fulfillment of works in the Municipal GAD of Baba Canton. The research methodology to be implemented was descriptive, developed in the administrative and financial area of ​​GAD Municipal Baba Canton, applying interviews and surveys to a population of 36 people. In relation to the results obtained in the investigation it was determined that there are important problems in the administrative and financial area since through them the objectives of the institution are met, the collection department does not keep up to date the list of users who are delayed, because the rental department does not manage the control of municipal taxes and the respective execution and thus provide necessary information